OZONATION PROCESS TO ENHANCE BIODEGRADABILTY OF PETROLEUM WASTE BY PSEUDOMONAS AERUGINOSA BACTERIA IN MINERAL SALT MEDIUM - Syafrizal Syafrizal; Chinta Pratama Saputra (Scientific Contributions Oil and Gas, 2014)
Contamination of petroleum waste has endangered the environment, yet its processing technology isnot effective and effi cient. It is becaused that by petroleum waste is diffi cult to be degraded by bacteria dueto many complex bonding compounds containned in this oil waste. Therefore, this study used ozonationas pretreatment process with the aim to enhance the biodegradation process. The variations in operatingconditions performed in this study are dose of ozone and pH. The bacteria used as a degrading agent isthe Pseudomonas aeruginosa. The results show thatozonation process can the enhancebiodegradabilityas indicated by the increase of degradation and population growths of bacteria. In addition, the abilityof the bacteria P. aeruginosa in degrading petroleum waste is varied with ozone doses and pH values.The highest percentage of degradation achieved at dose of 0.53 g ozone/h and pH 7.48 are approx from56.52% without ozone pretreatment to 79.32% after 7 days incubation.